2003
DOI: 10.1097/00005176-200311000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helicobacter pylori Infection on Growth of Children: A Prospective Cohort Study

Abstract: Among these lower-middle class children aged 12 to 60 months from a population with high prevalence of H. pylori infection, a new and sustained infection was followed by significant growth retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 21 publications
3
70
1
4
Order By: Relevance
“…The authors conclude that the effect of H. pylori on height is significant and irreversible. 4,24 The mechanisms by which H. pylori infection may affect growth have not been identified, but possible mechanisms such as dyspepsia and hypochlorhydria have been proposed. It has been suggested that this infection may reduce food intake because of its association with dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors conclude that the effect of H. pylori on height is significant and irreversible. 4,24 The mechanisms by which H. pylori infection may affect growth have not been identified, but possible mechanisms such as dyspepsia and hypochlorhydria have been proposed. It has been suggested that this infection may reduce food intake because of its association with dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, this association could be explained by respiratory infections being occasional manifestations of gastrointestinal infections during childhood. 4 The effect of H. pylori infection on children's growth may be related to the immune response on infection. Helicobacter pylori infection provokes an increase in some cytokines, therefore inducing chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H. pylori infection is contributed to the pathogenesis of gastritis, gastric and duodenal ulcer, gastric carcinoma, and mucosa associated lymphoid tissue lymphoma [3][4][5]. Moreover, H. pylori infection may be responsible for dyspeptic symptoms and decreased appetite [6,7]. It has been reported that successful eradication of H. pylori may be related with improved appetite and weight gain [8,9].…”
Section: Introductionmentioning
confidence: 99%